The case study as a teaching tool in management and accounting education - Carvalho, L.; Paiva, I. (II Internacional Forum on Management, 2018)
This paper aims to discuss the relevance of the case study methodology as a tool in management accounting education through the presentation of a case study on the Pestana Group. Case studies can be an effective learning tool in class and are popular in higher education, particularly, in business schools. They generally follow a narrative that includes: a problem or a question to solve; the description of the problem and some information about the company's background, sector, etc.; and some data to support the case study, such as, links to URls, images, videos, etc. The Pestana Group case study is based on its sustainability report. The Pestana Group is the largest hospitality company in Portugal. The analysis of this case in class will permit the discussion of strategic topics such as the disclosure of information in a sustainability report in the tourism industry. The case study is divided into three sections: first, we introduce the theoretical support about the use of case study methodology to teach management and accounting topics. Secondly, we present the instructional case study of the Pestana Group, learning objectives, learning outcomes and questions; and finally we conclude with some remarks and reflections.